Hubungan antara Pola Asuh Demokratis dengan Self Efficacy dalam Mahasiswa Melakukan Skripsi - Adytia Kurniawan; Muh.Abdurrouf; Retno Isroviatiningrum (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
The purpose of this study is to examine the extent to which parental democratic parenting style is related to students’ level of self-efficacy in completing their undergraduate thesis. Self-efficacy, or an individual’s belief in their ability to achieve specific goals, plays a crucial role in determining academic success, particularly in the thesis writing process. This research employed a quantitative approach with a cross-sectional design. The study involved a total of 141 student respondents, selected using a simple random sampling technique to ensure representativeness. The research instrument consisted of questionnaires designed to measure students’ perceptions of their parents’ parenting style and their self-efficacy levels regarding thesis completion. Data were analyzed using the Spearman Rank correlation test to identify the relationship between the independent and dependent variables. The results revealed that most respondents perceived their parents’ democratic parenting style as high, with 27 respondents (19.1%) categorized in this group. In addition, students’ self-efficacy levels were found to be predominantly high, with 132 respondents (93.6%). Statistical analysis showed a significant correlation between democratic parenting style and students’ self-efficacy in thesis completion, with a p-value of 0.001 (<0.05). The correlation coefficient was 0.289, indicating a moderate relationship. These findings suggest that democratic parenting, characterized by warmth, support, and open communication, plays an important role in shaping students’ confidence and belief in their ability to successfully complete academic tasks, particularly their undergraduate thesis. Thus, the study highlights the contribution of family environment as a supportive factor in enhancing students’ academic resilience and achievement.